'They are just beginning to think: who am I?' Health professionals on ill children's spirituality. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Llewellyn, Henry; Jones, Louise; Kelly, Paula; Craig, Finella; O'Gorman, Bernadette; Bluebond-Langner, Myra
Abstract : Background: There is widespread acknowledgement that care should include spirituality alongside physical, psychological and social aspects. Yet, little is known about how spiritual issues arise in conversations between healthcare professionals (HCPs), children and young people (CYP) and families and how they are managed in practice. The authors report qualitative data from a workshop with HCPs and faith leaders (FLs) which explored issues of concern to HCPs and FLs in anticipation of developing a community-based faith network across North Central London to meet these needs. Aim: To understand how HCPs conceptualise spirituality and their experiences in addressing spiritual issues as they emerge in practice. Method: Ethnographic participant-observation of a 1-day workshop to explore HCPs' (n=22) experiences of and attitudes towards spiritual issues and care for CYP and families; FLs (n=9) were present. Presentations and anonymised case scenarios were used to stimulate discussion. Presentations and discussions were audio-taped and transcribed verbatim. Four researchers recorded detailed field notes throughout the workshop. Data were analysed thematically. Results: Four themes emerged from statements by HCPs: (1) Concepts of spirituality (2) Loss (3) Roles (4) Conflicts and challenges. (1) While spirituality for adults and CYP was seen to encompass a search for meaning, hope, and a sense of connectedness to self, others and the world; it was assumed as underdeveloped in CYP. (2) HCPs described CYP and families' losses of future, meaning, relationships, hope and faith. (3) HCPs approached spiritual care by 'being there' for patients and families; supporting spiritual enquiry; signposting to specialists such as community FLs where appropriate. (4) Challenges included, trying to balance the ideal of openness with managing hope in the face of a poor prognosis. Conclusion: The way in which HCPs conceptualise spirituality in the context of CYP's development and multiple losses for CYP and families has implications for training including education in managing tensions between openness with CYP and respect for parents' wishes.